ENSURING THE RIGHTS AND FREEDOMS OF MILITARY SERVICEMEN OF THE ARMED FORCES OF UKRAINE UNDER THE LEGAL ORDER OF MARTIAL LAW - Poltiev, Yevheniy; Medvid, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this paper is to research the legal aspects of restrictions on constitutional rights and freedoms of military servicemen under the legal order of martial law, as well as explore the scientific approaches and requirements of the regulation in issues of determining the additional guarantees and restrictions of rights and freedoms of personnel that perform military service in the Armed Forces of Ukraine. Using general philosophical and scientific methods of cognition as the methodological basis for the study, the article provides an analysis of various scientific and doctrinal approaches to resolving the issues of social protection of servicemen under the legal order of martial law. One of the most significant methods that were implemented to highlight and establish the qualitative aspects of the phenomenon under study is the dialectic method of cognition. The results of the research indicate that additional guarantees and restrictions on the rights and freedoms of military personnel are objectively required, taking into consideration the specificity of the military service; furthermore, they relate to the appropriate fulfillment of military duties, maintenance of combat, and mobilization readiness of troops (forces). In addition, it was established that the current state of legislation and mechanisms in Ukraine in this area is not perfect. Moreover, it has been determined that while Ukraine’s current legislation and administrative processes are not optimal, they provide the possibility of ensuring that military personnel receive the minimum amount of social protection. Discussion: the research indicates that military personnel’s constitutional rights and freedoms are restricted under the martial law judicial system. These limitations are enforced by legal regulations that apply to the fundamental principles of state policy regarding military personnel’s social welfare and military service regulations. It has been established that the special legal and constitutional status of military personnel is caused by the fact that the fulfillment of military service responsibilities and the specifics of military service cause limitations to be applied to an individual’s legally granted constitutional rights and freedoms. Furthermore, under martial law, military personnel are impacted by military legislation that restricts their individual constitutional rights, which include the right to take leave, dismissal from military service, and pension provision. However, this legislation also establishes additional guarantees for military personnel (for instance, increased allowances and one-off financial aid due to deaths). Moreover, it concluded that the current legislation in this area required a balanced improvement, which becomes possible by taking into consideration the most recent advancements in domestic science and international legal regulations in the relevant field.